Unbalanced oxidant-induced DNA damage and repair in COPD: a link towards lung cancer. Issue 6 (2nd April 2011) - Caramori, Gaetano; Adcock, Ian M; Casolari, Paolo; Ito, Kazuhiro; Jazrawi, Elen; Tsaprouni, Loukia; Villetti, Gino; Civelli, Maurizio; Carnini, Chiara; Chung, Kian Fan; Barnes, Peter J; Papi, Alberto
Abstract : Background: Chronic obstructive pulmonary disease (COPD) is characterised by oxidative stress and increased risk of lung carcinoma. Oxidative stress causes DNA damage which can be repaired by DNA-dependent protein kinase complex. Objectives: To investigate DNA damage/repair balance and DNA-dependent protein kinase complex in COPD lung and in an animal model of smoking-induced lung damage and to evaluate the effects of oxidative stress on Ku expression and function in human bronchial epithelial cells. Methods: Protein expression was quantified using immunohistochemistry and/or western blotting. DNA damage/repair was measured using colorimetric assays. Results: 8-OH-dG, a marker of oxidant-induced DNA damage, was statistically significantly increased in the peripheral lung of smokers (with and without COPD) compared with non-smokers, while the number of apurinic/apyrimidinic (AP) sites (DNA damage and repair) was increased in smokers compared with non-smokers (p=0.0012) and patients with COPD (p<0.0148). Nuclear expression of Ku86, but not of DNA-PKcs, phospho-DNA-PKcs, Ku70 or γ-H2AFX, was reduced in bronchiolar epithelial cells from patients with COPD compared with normal smokers and non-smokers (p<0.039). Loss of Ku86 expression was also observed in a smoking mouse model (p<0.012) and prevented by antioxidants. Oxidants reduced (p<0.0112) Ku86 expression in human bronchial epithelial cells and Ku86 knock down modified AP sites in response to oxidative stress. Conclusions: Ineffective DNA repair rather than strand breakage per se accounts for the reduced AP sites observed in COPD and this is correlated with a selective decrease of the expression of Ku86 in the bronchiolar epithelium. DNA damage/repair imbalance may contribute to increased risk of lung carcinoma in COPD.